Psoriasiform Diaper Rash Possibly Induced by Oral Propranolol in an 18-Month-Old Girl with Infantile Hemangioma - Raphaëlle Baggio; Claire Le Treut; Laure Darrieux; Amélie Vareliette; Gilles Safa (Karger Publishers, 2016)
Propranolol, a nonselective blocker of β-adrenergic receptors, has become the first-line treatment for complicated infantile hemangiomas. Therefore, its use in the pediatric population has expanded in recent years. In adults, β-blockers have been reported to be the most common causative agents for drug-induced psoriasis. In infants treated with propranolol for infantile hemangioma, the onset of psoriasiform diaper rash has not yet been reported. Here, to the best of our knowledge, we report the first case of psoriasiform diaper rash possibly induced by oral propranolol in an 18-month-old girl with no family history of psoriasis.